Recepcja twórczości Czesława Miłosza na Białorusi - Kazłouskaya, Maryna; Pushkina, Maria (Postscriptum Polonistyczne, 2020)
The article is dedicated mainly to the reception of Czesław Miłosz’s works in Belarus. Analyzed here is the history of Belarussian translations and some strategies of translation determining the selection of certain poems and essays. The article also aims to elucidate the specificity of readers response to Czesław Miłosz’s poetry and prose as well as to describe Belarussian literary research on the works of the Polish writer.